Financial Information Transparency of EGovernment in Bandung City and its Effect on Public Trust - Arwati, Dini; Verdania Latif, Dini (International Journal of Psychosocial Rehabilitation, 2020)
E-government is a system based on technology and information that aims to improve the function of public administration and relations with the public. With the government, it is hoped that information transparency will be created, especially financial information. A nontransparent system can result in budget misuse, resulting in high levels of corruption. Survey results at the global level show that there are cases of corruption that cause distrust of the government. This study aims to determine the effect of information transparency on public trust. The research method used is a survey method with a quantitative approach. The survey was conducted by distributing questionnaires to 200 residents of Bandung. The results of the study show that transparency regarding the transparency of the budget and implementation policies has no effect on public trust. While transparency of information regarding the process of preparing and implementing a budget influences public trust. It can be concluded that the public pays more attention to the results of government real work. The public should also pay attention to policies, because the key to preparing and implementing the budget starts with the policy.